Meningkatkan Hasil Belajar Siswa dengan Menggunakan Metode Demontrasi dalam Pembelajaran Seni Tari di SMA Negeri 13 Sijunjung - Sinta Kartika; Fuji Astuti (SENDRATASIK UNP, 2023)
This study aims to improve student learning outcomes by using the demonstration method in learning dance at SMA Negeri 13 Sijunjung. The type of research used is classroom action research. The research instruments were observation sheets, post-test cycles and skills tests. Data collection techniques are carried out by means of observation, literature study, and documentation. Data were analyzed using the percentage formula. The average student learning activity in cycle I was 67% with good enough criteria. After making improvements in cycle II, the average student learning activity increased by 90% with very good criteria. Students who were previously less active and did not want to move and were shy in making movements, after the demonstration method was applied students became confident.